Pengaruh Kualitas Pelayanan dan Persepsi Risiko terhadap Kepuasan Pelanggan PT Lion Parcel Mahkota 53 Batam - Beny Beny; Winda Evyanto (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this study is to determine the effect of service quality and perceived risk on customer satisfaction at PT Lion Parcel Mahkota 53 Batam. The technique used in this study is a saturated sample technique with a total of 104 respondents. The measuring instrument used is a 5 (five) Likert scale point. The method of data analysis was carried out using multiple linear regression analysis. The data quality test in this study used a validity test, reliability test, classical assumption test in this study using normality test research, multicollinearity test and heteroscedasticity test and influence test using multiple linear regression analysis and coefficient of determination analysis (R2), while hypothesis testing in this study uses the t test and F test. Results of this study, attest that service quality, risk perception has a positive effect on customer and the quality of service, the perception of risk together has an influence on customer.